The Role of the Economic Crisis to Expand the Public Sector - (:unkn) unknown (Peter Lang AG, 2019)
The small size of the public sector has long been seen as the key to economic growth. However, it is seen that public expenditures have an increasing tendency. As one of the reasons for this situation, we can show liberal economy. The liberal economy, which is ironically trying to keep state intervention to a minimum, can also be the cause of this situation. High-risk capital causes crises from time to time. In such cases, the public sector is seen as a savior. And the public sector loves to intervene in the economy and uses every opportunity to grow. So, this study aims to demonstrate the impact of economic crises in the rise of public spending and criticizing the savior role of the public sector. Public spending in times of crisis can have positive effects in the short term. But in the long term, the effects of the large public sector on the economy should be discussed. Because, if public spending increases once, it is very difficult to draw it back to its former level. © 2019 Peter Lang GmbH.
Keywords: Economic Crisis; Private Sector; Public Spending